دور إدارة الجودة الشاملة في تحقيق الميزة التنافسية المستدامة: بحث استطلاعي في شركة التأمين العراقية العامة (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Seeks this research is to clarify the role played by TQM represented Bmngaradtha (commitment and support of senior management of the philosophy of TQM, strategic planning for the overall quality, focus on the customer, continuous improvement, post workers, training and rehabilitation of workers) to achieve sustainable competitive advantage represented by dimensions (estimated intrinsic , creative culture, information technology, strategic flexibility), research has relied on the views of a sample of managers working in the Iraqi public insurance company. So identified research problem in answering the following questions: "What is the size of visualization owned by managers in the company surveyed the principles of Total Quality Management? What is the nature TQM principles in the company surveyed? Does the managers in the company surveyed a clear vision for the role of TQM to achieve dimensions of sustainable competitive advantage?The research aims to achieve several objectives, including increasing awareness of the concepts of total quality management and sustainable competitive advantage in a service environment Iraqi, especially in the company surveyed, provide a future vision of the possibility of success, and the actual application of the principles of total quality management in the insurance sector.      The researcher adopted a default model was built after a review and analysis of the relevant literature in the context of two hypotheses main points at the origin of a group of sub-hypotheses.     The research was presented a set of conclusions and recommendations that are consistent with the results of the analysis of the most important of these conclusions was: turns out that there is a relationship and influence between the principles of total quality management and sustainable competitive advantage in the company in question and accept the research hypotheses.         While the research was presented recommendation that the need to adopt IT service companies TQM as administrative sophisticated method instead of traditional methods of management, in order to reach continuous improvement at all levels of activity of the company.